Evaluation and health risk analysis of potential toxic elements in select foods vended within a university campus in southeastern Nigeria - Amara Miracle Olaleye; Stanley Ugochukwu Nwoke; Dozie John Okongwu; Nancy Amaraegbulam; Chukwuemeka Cornelius Ezeh; Ifeanyi Adolphus Ucheana (Journal of Trace Elements and Minerals)
Background: Bambara nut pudding (BNP) and cowpea bean cake (BC) are popular street-vended foods on Nigerian University campuses. Current study seeks to investigate the concentrations and associated health risks of cadmium (Cd), lead (Pb), chromium (Cr), and nickel (Ni) in BNP and BC consumed within a university campus in southeastern Nigeria. Method: The potentially toxic elements (PTE) in the food samples were quantified using atomic absorption spectrometry (AAS), while health risks were assessed using carcinogenic and non-carcinogenic health risk models. Calibration curves for the elements were plotted using 1, 2, and 3 mg L–1. Method validation included recovery analysis, with instrument sensitivity assessed through limits of detection (LOD) and quantification (LOQ). Results: Mean PTE concentrations (mg kg⁻¹) in BNP were Cd (0.13–2.94), Cr (4.33–51.09), Ni (0.35–2.15), and Pb (5.27–307.62), while BC levels ranged as Cd (ND–2.54), Cr (14.51–36.20), Ni (ND–2.41), and Pb (3.36–6.49). Both foods' Cd, Cr, and Pb levels exceeded WHO thresholds. A significant difference was recorded between Cd, Cr, and Pb concentrations in both foods (p<0.05). Non-carcinogenic risk (THQ/THI >1) was detected in 64 % of BNP and 36 % of BC samples, indicating elevated exposure hazards. Carcinogenic risks were identified for Cr, Ni, and Cd, with cancer risk values surpassing tolerable limits (1 × 10⁻⁶). Conclusion: This study identifies significant contamination of BNP and BC by PTEs, particularly Pb and Cr, linked to vendor practices and environmental sources. It underscores urgent regulatory measures to mitigate health risks, adoption of HACCP protocols, and advocates continuous monitoring of street-vended foods.